2013
DOI: 10.1007/s40519-013-0067-2
|View full text |Cite
|
Sign up to set email alerts
|

Disgust, contempt, and anger and the stereotypes of obese people

Abstract: Overall, these findings provide further evidence that disgust plays an important role in prejudice toward obese people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 23 publications
4
33
0
4
Order By: Relevance
“…Other authors have showed that physical disgust was a good predictor of negative attitudes toward obese individuals (O"Brien, et al, 2013). All these works suggest that physical disgust plays a central role in the explanation of antifat attitudes (Vartanian, Thomas, & Vanman, 2013).…”
Section: Disgustmentioning
confidence: 89%
See 1 more Smart Citation
“…Other authors have showed that physical disgust was a good predictor of negative attitudes toward obese individuals (O"Brien, et al, 2013). All these works suggest that physical disgust plays a central role in the explanation of antifat attitudes (Vartanian, Thomas, & Vanman, 2013).…”
Section: Disgustmentioning
confidence: 89%
“…The reason for the election of a sample composed only by women is based on the fact that it has been found that antifat attitudes are just related with physical disgust in the case of female participants (Vartanian et al, 2013). This result may be explained by the sociocultural differences about thinness internalization found between women and men.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, part of stigma is its effect on a person's body and mind (e.g., higher levels of depression and cortisol levels in those who are stigmatized, feelings of disgust in those who stigmatize). 3,13,14 This thinking also reveals that stigma is evident in objects in the environment (e.g., equipment that fits only some bodies, images of thin people used in advertising), 7 in what a person can do, and in how a person can live (e.g., reduced employment opportunities, social standing, dating opportunities). 15 In health care specifically, stigma is apparent in decision making, interpersonal interactions, care judgments, personal perceptions, quality of professional practice, avoidance of health care by those who feel stigmatized, and a lack of trust in health care providers.…”
Section: How Can Physiotherapists Develop a Greater Understanding Of mentioning
confidence: 99%
“…There was however the possibility that some participants may have found the video's content too sensitive or offensive, and instead of evoking empathy the video content may only have activated negative feelings (repulsion/disgust) and discomfort for the participants. Perhaps in attempting to evoke empathy participants were reminded of (1) negative experiences with individuals who are overweight/obese; or (2) In a study by Vartanian, Thomas and Vanman (2013), participants indicated the extent to which they felt disgust, contempt and anger toward people who are obese. Of the three emotions only disgust was a significant positive predictor of obesity stereotypes, and therefore shown to play an important role in negative attitudes toward people who are obese.…”
Section: Problems With Research and Theorymentioning
confidence: 99%